Adeno-associated virus-binding antibodies detected in cats living in the Northeastern United States lack neutralizing activity - Adachi, Kei (Sci Rep, 2020)
Cats are a critical pre-clinical model for studying adeno-associated virus (AAV) vector-mediated gene therapies. A recent study has described the high prevalence of anti-AAV neutralizing antibodies among domestic cats in Switzerland. However, our knowledge of pre-existing humoral immunity against various AAV serotypes in cats is still limited. Here, we show that, although antibodies binding known AAV serotypes (AAV1 to AAV11) are prevalent in cats living in the Northeastern United States, these antibodies do not necessarily neutralize AAV infectivity. We analyzed sera from 35 client-owned, 20 feral, and 30 specific pathogen-free (SPF) cats for pre-existing AAV-binding antibodies against the 11 serotypes. Antibody prevalence was 7 to 90% with an overall median of 50%. The AAV-binding antibodies showed broad reactivities with other serotypes. Of 44 selected antibodies binding AAV2, AAV6 or AAV9, none exhibited appreciable neutralizing activities. Instead, AAV6 or AAV9-binding antibodies showed a transduction-enhancing effect. AAV6-binding antibodies were highly prevalent in SPF cats (83%), but this was primarily due to cross-reactivity with preventive vaccine-induced anti-feline panleukopenia virus antibodies. These results indicate that prevalent pre-existing immunity in cats is not necessarily inhibitory to AAV and highlight a substantial difference in the nature of AAV-binding antibodies in cats living in geographically different regions.